2022
DOI: 10.1590/1984-0462/2022/40/2020420in
|View full text |Cite
|
Sign up to set email alerts
|

Excessive use of social media by high school students in southern Brazil

Abstract: Objective: To assess the prevalence of excessive use of social media and associated factors, as well as possible health consequences in high school students in southern Brazil. Methods: This is a population-based cross-sectional study, conducted with high school students in the city of Rio Grande, RS. All students who were attending high school at the Federal Institute of Rio Grande do Sul, campus Rio Grande, were eligible for this research in the second semester of 2019. In total, 513 students participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
0
0
1
Order By: Relevance
“…This study observed that back and neck pain was the most prevalent symptoms among female students [25]. Studies [26] reported that the frequent and excessive use of the Internet could cause certain physical complaints among undergraduate students, such as headache, back pain, finger numbness, and neck pain; however, the complaints of back pain and neck pain were consistent in this study.…”
Section: Discussionsupporting
confidence: 75%
“…This study observed that back and neck pain was the most prevalent symptoms among female students [25]. Studies [26] reported that the frequent and excessive use of the Internet could cause certain physical complaints among undergraduate students, such as headache, back pain, finger numbness, and neck pain; however, the complaints of back pain and neck pain were consistent in this study.…”
Section: Discussionsupporting
confidence: 75%
“…Revista de Gestão e Secretariado -GeSec, V. 15, N. (Vieira et al, 2022;Gonçalves et al, 2023;Cortés et al, 2021;Fagundes et al, 2020). Três artigos (30%) abordaram como a tecnologia influencia na construção da identidade dos adolescentes Dias et al, 2017;Lima et al, 2016).…”
Section: Figuraunclassified
“…Entretanto, considerando que a autopercepção influencia a forma como o indivíduo se apresenta nas redes, é importante destacar a oportunidade oferecida aos usuários de se mostrarem de maneira que ajuste sua imagem aos seus objetivos e necessidades de interação social (Vieira et al, 2022). Porém, há uma tendência de se engajar sempre em uma auto apresentação socialmente desejável, o que faz com que os usuários fujam de sua realidade para se manifestar de forma idealizada, enfatizando traços atrativos (Fagundes et al, 2020).…”
Section: Figuraunclassified
See 1 more Smart Citation
“…A terminologia saúde mental é amplamente utilizada, principalmente na área da saúde mental, tanto em meios de comunicação quanto em ambientes psiquiátricos e psicoterapêuticos. Ao longo do tempo, houve debates sobre como definir essa terminologia (Alcântara;Vieira;Alves, 2022). Nos seus relatórios, a Organização Mundial da Saúde (OMS, 2013, p. 09), compreende a saúde mental como "[...] um estado de bemestar no qual o indivíduo perceba as suas próprias capacidades, possa lidar com as tensões normais da vida, possa trabalhar de forma produtiva e frutífera e possa contribuir para a sua comunidade".…”
Section: Introductionunclassified